2017
DOI: 10.3174/ajnr.a5295
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of DSC MRI Echo Times for CBV Measurements Using Error Analysis in a Pilot Study of High-Grade Gliomas

Abstract: Background and Purpose To minimize the variance in CBV measurements made with DSC-MRI, the optimal echo time must be calculated. Simulations can be used to determine the influence of TE on CBV but may not adequately recapitulate the in vivo heterogeneity of pre-contrast T2*, contrast agent (CA) kinetics, and biophysical basis of CA induced T2* changes. With multi-echo based DSC-MRI acquisitions, voxel-wise pre-and post-contrast T2* changes can be quantified and used to compute the optimal TEs for traditional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that the AIF is adversely impacted by concurrent T 1 effects, which can substantially reduce the resulting CBF measures (up to 40%) . In addition, the optimal TE for measuring the AIF was previously estimated to be 12 ms, which is far shorter than both the typical DSC‐MRI protocol and the reported optimal tumor TE (30 ms) . Multi‐echo sequences may permit the optimization of individual echoes for AIF and tissue, particularly when at least 1 TE is less than 15 ms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the AIF is adversely impacted by concurrent T 1 effects, which can substantially reduce the resulting CBF measures (up to 40%) . In addition, the optimal TE for measuring the AIF was previously estimated to be 12 ms, which is far shorter than both the typical DSC‐MRI protocol and the reported optimal tumor TE (30 ms) . Multi‐echo sequences may permit the optimization of individual echoes for AIF and tissue, particularly when at least 1 TE is less than 15 ms.…”
Section: Discussionmentioning
confidence: 99%
“…38 In addition, the optimal TE for measuring the AIF was previously estimated to be 12 ms, which is far shorter than both the typical DSC-MRI protocol and the reported optimal tumor TE (30 ms). 39 Multi-echo sequences may permit the optimization of individual echoes for AIF and tissue, particularly when at least 1 TE is less than 15 ms. Finally, the correlation between individual echoes in multi-echo protocols may serve as a unique criterion to improve automated AIF selection.…”
Section: Discussionmentioning
confidence: 99%
“…To balance these effects, the typical recommendation for TE is 25-35 ms. Using rCBV error minimization as a metric for TE optimization, the optimal TE is equal to a weighted average of the changes in tissue T 2 * during contrast agent passage (Bell et al, 2017a;Boxerman et al, 1997;Thilmann et al, 2004). Due to the bolus-induced signal drop, this is lower than the baseline T 2 *…”
Section: Pulse Sequencesmentioning
confidence: 99%
“…The simplest of these options is a dual GRE, where an additional short-TE echo is acquired between the excitation pulse and the traditional longer-TE echo. This method also provides more flexibility in the TEs, which may improve characterization of both the AIF (using an optimized shorter TE) and brain tissue (Bell et al, 2017a;Newton et al, 2016). Perhaps more importantly, T 1 leakage effects can be quantified, permitting both direct DCE-MRI analysis and correction of DSC-MRI data for more accurate perfusion analysis (Quarles et al, 2012;Sourbron et al, 2009;Stokes et al, 2016a).…”
Section: Pulse Sequencesmentioning
confidence: 99%
“…As NAWM ROIs are conventionally drawn contralateral to tumor tissue, we selected the contralateral mask hemisphere. Additional details of these postprocessing steps can be found in previous publications …”
Section: Methodsmentioning
confidence: 99%